Application of Semi-Fowler Position and Pursed Lip Breathing in Pulmonary Tuberculosis Patients with Inefective Breathing Pattern Problems in the Mawar Room, Rsud X - Niken Sephia Marshanda; Shindi Hapsari (Jurnal EduHealth, 2026)
Pulmonary Tuberculosis remains a significant health problem and is often associated with respiratory complications such as ineffective breathing patterns. This case study aimed to describe the effectiveness of non-pharmacological nursing interventions, namely the Semi- Fowler position and Pursed-Lip Breathing exercises, in improving breathing patterns in patients with Pulmonary Tuberculosis. A descriptive case study design was applied to three patients treated in the Mawar Ward of RSUD X. Data were collected through interviews, observation, physical examination, and documentation over a three- day intervention period. Outcomes were evaluated based on respiratory rate, oxygen saturation, use of accessory respiratory muscles, chest wall retraction, and subjective dyspnea. The results showed a decrease in respiratory rate from 26–28 to 20–21 breaths per minute and an increase in oxygen saturation from 94–95% to 99%, accompanied by reduced dyspnea and improved breathing patterns. These findings indicate that the Semi-Fowler position combined with Pursed-Lip Breathing is effective in improving respiratory function in patients with Pulmonary Tuberculosis.